Did the Philippine Islands have a currency board during the American colonization period? - FREEDMAN, Ryan (Turkish Economic Review, 2018)
Abstract. The Philippine monetary system and data from 1903-1948are examined, using general observations and statistical tests to determine to what extent the system operated as a currency board. This paper makes detailed annual balance sheets of the monetary system available in machine-readable form for the first time, in a companion Excel workbook. Keywords. Philippines, Currency board, Gold standard fund, Currency reserve fund, Exchange standard fund. JEL. E59, N15.